Preferensi Petani dan Konsumen terhadap Gabah, Beras dan Nasi dari 10 Varietas Unggul Baru di Kabupaten Serang Provinsi Banten - Kurniawati, Sri; Susanti, Eka Yuli; Noviastuti, Nindia; Giamerti, Yuti; Yursak, Zuraida; Susilawati, Pepi Nur (Agropross : National Conference Proceedings of Agriculture, 2022)
Preference information on New Superior Varieties (NSV) characteristics such as grain, rice and rice is needed for NSV development in an area. The purpose of this study was to determine the preferences of farmers and consumers towards grain, rice and rice from 10 NSV in Serang Regency, Banten Province. The varieties tested were Inpari 32, Inpari 42, Inpari 43, Inpari 45, Inpago 8, Inpari IR Nutri Zinc, Mantap, Padjajaran, Siliwangi and Tarabas. The method of data collection was carried out using a questionnaire to 36 respondents who were selected intentionally (purposive sampling). The questionnaire was made with an ordinal scale, respondents chose the answers strongly dislike, dislike, somewhat like, like and really like the characteristics of grain, rice and cooked rice. Furthermore, the data is processed and analyzed by Friedman Test. The results showed that there were 4 most preferred varieties based on the characteristics of grain, rice and cooked rice, namely Inpari 45, Tarabas, Inpari 32 and Mantap. The results of this study are expected to be used as a basis for selecting varieties for seed development in Serang Regency, Banten.